Analisis Efektifitas Pursed Lip Breathing dan Balloon Blowing untuk Meningkatkan Saturasi Oksigen pada Pasien COPD (Chronic Obstructive Pulmonary Disease): Analysis of Effectiveness of Pursed Lip Breathing and Balloon Blowing to Increase Oxygen Saturation in COPD (Chronic Obstructive Pulmonary Disease) Patients - Salva Dwi Kosayriyah; Vivin Nur Hafifah; Zainal Munir; Handono Fatkhur Rahman (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
ABSTRACT Background: COPD (Chronic Obstructive Pulmonary Disease) is one of the deadliest diseases in the world that causes various lung disorders such as dyspnea, so that if left unchecked it can decrease oxygen saturation in the body. Non Pharmacological interventions such as Pursed Lip Breathing and Balloon Blowing can help COPD patients reduce dyspnea. Objective: to analyze the effectiveness of Pursed Lip Breathing and Balloon Blowing to Increase Oxygen Saturation in COPD Patients. Methods: database search includes Google Scholar, Science Direct and Proquest with keywords Pursed Lip Breathing, Balloon Blowing, COPD / PPOK. The criteria for the articles chosen were published in 2016-2020 with full text, in Indonesian or English with experimental article types, this Systematic Review uses 15 articles that match the criteria. Results: Analysis of fifteen articles showed that many COPD (Chronic Obstructive Pulmonary Disease) patients had decreased oxygen saturation due to dyspnea. Several studies have shown that pursed lip breathing and balloon blowing can increase oxygen saturation and reduce respiratory frequency. Sugestion: Pursed Lip Breathing and Balloon Blowing are nonpharmacological therapies with easy techniques that are very effective in helping COPD patients reduce their dyspnea, resulting in increased oxygen saturation. Keywords: Pursed Lip Breathing, Balloon Blowing, COPD ABSTRAK Pendahuluan : COPD (Chronic Obstructive Pulmonary Disease) merupakan salah satu penyakit mematikan di dunia yang menyebabkan berbagai gangguan pada paru-paru seperti dispnea, sehingga jika dibiarkan terus-menerus dapat menurunkan saturasi oksigen dalam tubuh. Intervensi non Farmakologi seperti Pursed Lip Breathing dan Balloon Blowing dapat membantu pasien pasien COPD dalam mengurangi dispnea. Tujuan : untuk menganalisis Efektifitas Pursed Lip Breathing dan Balloon Blowing untuk Meningkatkan Saturasi Oksigen pada Pasien COPD. Metode: pencarian database meliputi Google Scholar, Science Direct dan Proquest dengan kata kunci Pursed Lip Breathing, Balloon Blowing, COPD/PPOK. Kriteria artikel yang dipilih yaitu terbit tahun 2016-2020 dengan teks penuh, berbahasa Indonesia atau inggris dengan jenis artikel eksperimental, Systematic Review ini menggunakan 15 artikel yang sesuai dengan kriteria. Hasil: Analisis dari lima belas artikel menunjukkan bahwa banyak pasien COPD (Chronic Obstructive Pulmonary Disease) yang mengalami penurunan saturasi oksigen karena dispnea. Beberapa hasil penelitian menunjukkan bahwa pursed lip breathing dan balloon blowing dapat meningkatkan saturasi oksigen dan menurunkan frekuensi pernapasan. Kesimpulan: Pursed Lip Breathing dan Balloon Blowing merupakan terapi nonfarmakologis dengan teknik mudah yang sangat efektif membantu pasien COPD dalam mengurangi dispnea hingga berdampak pada peningkatan saturasi oksigen. Kata kunci : Pursed Lip Breathing, Balloon Blowing, COPD/PPOK